Factor XI Dependent and Independent Activation of Thrombin Activatable Fibrinolysis Inhibitor (TAFI) in Plasma Associated with Clot Formation - Bouma, Bonno N.; Mosnier, Laurent O.; Meijers, Joost C. M.; Griffin, John H. (Thrombosis and Haemostasis, 1999)
Thrombin Activatable Fibrinolysis Inhibitor (TAFI) also known as plasma procarboxypeptidase B is activated by relatively high concentrations of thrombin in a reaction stimulated by thrombomodulin. In plasma an intact factor XI-dependent feed back loop via the intrinsic pathway is necessary to generate sufficient thrombin for TAFI activation. This thrombin generation takes place after clot formation with consequent down-regulation of fibrinolysis. We developed a specific and sensitive assay for activated TAFI (TAFIa) and studied its factor XI-dependent generation during clot formation. In the absence of thrombomodulin, addition of 20 nM thrombin to normal plasma generated 5-10% of the amount of TAFIa generated by 20 nM thrombin in the presence of 8 nM thrombomodulin. Minimal activation of TAFI was detected in factor II deficient plasma when clotting was initiated by 20 nM thrombin. Addition of 320-640 nM of thrombin to factor II deficient plasma resulted in the same amount of TAFIa as in normal plasma, suggesting that ~50% of factor II has to be converted to thrombin for extensive activation of TAFI. A Mab that neutralizes activated factor XII had no effect on TAFI activation indicating that an intact contact system is not necessary for the activation of TAFI. The dependency of TAFI activation of factor XI was tested using a Mab that neutralizes activated factor XI. When plasmas from 13 healthy individuals were tested, this Mab reduced TAFI activation by 65% (range 35-89%). Our results indicate that activation of TAFI in serum after clot formation can be quantitated and that it takes place in both factor XI-dependent and factor XI-independent mechanisms.
Keywords: Factor XI; TAFI; fibrinolysis